PINK1 phosphorylates ubiquitin predominantly in astrocytes - Barodia, Sandeep K. (NPJ Parkinsons Dis, 2019)
Loss-of-function mutations in PINK1 are causally linked to recessively inherited Parkinson’s disease (PD), with marked loss of dopaminergic neurons in the substantia nigra that are required for normal movement. PINK1 is a nuclear-encoded mitochondrial-targeted kinase that phosphorylates a conserved serine at amino acid 65 (pS65) in ubiquitin as well as Parkin, another gene with loss-of-function mutations linked to recessive parkinsonism. The steady-state levels of PINK1 protein are very low, even in cells that express PINK1, because PINK1 is normally targeted for degradation after mitochondrial import by a process that is dependent upon mitochondrial membrane potential. Dissipation of the mitochondrial membrane potential with ionophores, such as CCCP and valinomycin, causes the accumulation of PINK1 on the outer mitochondrial membrane, a marked increase of pS65-ubiquitin and the recruitment of Parkin, which targets dysfunctional mitochondria for degradation by autophagy. While the high penetrance of PINK1 mutations establish its critical function for maintaining neurons, the activity of PINK1 in primary neurons has been difficult to detect. Mounting evidence implicates non-neuronal cells, including astrocytes and microglia, in the pathogenesis of both idiopathic and inherited PD. Herein we used both western analysis and immunofluorescence of pS65-ubiquitin to directly compare the activity of PINK1 in primary neurons, astrocytes, microglia, and oligodendrocyte progenitor cells cultured from the brains of wild-type (WT) and PINK1 knockout (KO) rat pups. Our findings that PINK1-dependent ubiquitin phosphorylation is predominantly in astrocytes supports increased priority for research on the function of PINK1 in astrocytes and the contribution of astrocyte dysfunction to PD pathogenesis.